Villa Tiburtina: storia di un servizio di psicoterapia all’Università - Fiori Nastro, Paolo; Righetti, Valentino; Masillo, Alice (Il sogno della farfalla, 2020)
This article deals with the story of an “External mental health unit” at the University of Rome, where the Analisi Collettiva’s seminars started in 1975. Over the years, this Unit changed location and was renamed Psychotherapeutic Operational Department Unit (U.O.D) “Villa Tiburtina”. In this latter seat, physically far from the Psychiatric department and the University hospital, the psychiatrists managed to turn into daily clinical practice what experienced in their personal formation during the Analisi Collettiva. They succeeded in carrying out a psychotherapeutic practice which enabled the patient’s cure and also psychiatrists’ personal training. This realization was further accomplished thanks to clinical supervision, and research opportunities which through national and international collaborations laid the groundwork to acquire the scientific research methodology.